The Impact of Compensation and Religiosity on Fraudulent Behavior in MSMEs: The Role of Islamic Work Ethics as a Moderator - Faisal, Yusuf; Herawati, Mesi; Athaillah, Ahmad; Gumala Sari, Egi (International Journal of Islamic Business and Economics (IJIBEC), 2024)
This study aims to obtain empirical evidence on the effect of compensation and religiosity on fraudulent behavior with Islamic work ethics as a moderating variable. This study uses a quantitative research type. This study used a questionnaire distributed to MSMEs in West Java, namely 350 questionnaires distributed directly. Each questionnaire distributed contains 114 statements that respondents must answer. From the distribution of the questionnaire, 207 respondents provided answers. To obtain the results of this study, the researcher used PLS-SEM Version 3.0. This study found that compensation has a significant negative effect on fraudulent behavior, religiosity has a significant negative effect on fraudulent behavior, Islamic work ethics cannot moderate the relationship between compensation and fraudulent behavior, and Islamic work ethics moderates the relationship between religiosity. It cannot moderate the relationship between fraudulent behavior. This research provides information regarding fraudulent behavior, which is new research discussing the relationship between religiosity, which is the basis of the character of the Prophet Muhammad SAW